Prioritization of Socio-Ecological Indicators for Adaptation Action in Pauri District of Western Himalaya - Shashidhar Kumar Jha; Ajeet Kumar Negi; Rajendra Singh Negi; Juha Mikael Alatalo; Mani Bhushan Jha (World, 2023)
Socio-ecological systems have increasingly faced climate-change impacts, which have adversely affected the lives and property of inhabitants. The present study aims to prioritize adaptation actions along an altitudinal gradient (<1200 m asl (Zone A), 1201–1800 m asl (Zone B), and >1801 m asl (Zone C)) in Pauri District, Uttarakhand. A cross-sectional survey research design was employed to prioritize adaptation action from 545 randomly selected households in 91 villages. A multi-disciplinary bottom-up indicator-based approach was applied to identify and normalize sectoral indicators, and PCA was used to prioritize sectoral indicators. Adaptation actions were designed with prioritized sectoral indicators along the altitude and stakeholder consultations. The prioritized indicators varied along the altitudinal gradient, and more than 50% of the indicators for the same sector were different along an altitudinal gradient. Sectoral adaptation planning along the altitude is pertinent in the mountain because they contribute to adaptation planning differently. Additionally, the mainstreaming of adaptation strategies with national and regional development measures is also required. Finally, cross-sectoral resource management that combines users, planners, scientists, and policymakers should be formulated along the altitude within the district. These findings contribute to minimizing the gap between policy/program fabrication and local requirements. The evidence-based valuable knowledge for decision-makers could enable Himalayan communities to adapt to the impacts of climate change effectively. Adaptation planning is also critical for designing adaptation projects for the Green Climate Fund, Adaptation Fund, and funds from multilateral and bilateral agencies. It will facilitate Nationally Determined Contributions, which aims to adapt better to climate change by enhancing investments in development programs in vulnerable sectors.